(3JdNjU GdeLSWi hJgPjHIs - (3GdbRhjfj , Ydj Hf YeQ Hf Ydj GdcGJHj, fLe GdOjf,J (B675 (3g` s ((3eOjfI OGQ Gdedc bhfjI s)
(3ChdgG (B:s
(3GdMeO dhGgH GdYbd heajV GdYOd hHYO ,adeG UMHfi eOI ef GdReGf CYRQ abGFi Ydi , hChdGge HGdEMSGf Edjg dOi , hgh Ydi Hf YeQ Hf Ydi GdbRhjfi HGMKoG Yf GdYdhe GdMbjbI s
(3BNQgG (B:s
(3gh GdNW GdhGUd Hjf bOefG hHjf CUd GdefGQI adCf bhSi BH fM eJSGhjJGf aMSGHgeG eJSGhjGf hPdc eG CQOfG HjGfg , hgPG BNQ GdcJGH s
(3Cdag GdeDda dYdi Hf YeQ Hf Ydi GdbRhjfis
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3HChdgG agQS HGdeMJhjGJs
(3HgG fXGe GdJYbjHI s
(3HgG CTcGd hQShe s
(3bQf GdfSN (B:s
Keywords: (3Gdadcs